China's Energy Security and the Geopolitical Impact of Renewable Energy Strategies : A Case Study on Cobalt Mining in DRC - Peters, Kaitlyn Marie (2022)
Driven by the need to account for long-term climate change risks and opportunities, a global energy transformation driven by increased adoption of renewable energy sources is underway globally. This transition will have significant geopolitical implications by shifting the power dynamics and relations between states, and affecting the social, economic, and geographic drivers of security. The influence of states which have invested heavily in renewable technologies will change as they built up their production and export capacity. The security of critical mineral supply chains is a strategic issue due to the expected growth in demand caused by adoption of clean energy technologies worldwide. China has committed robust state resources to develop its renewable energy sources and maintains a strong presence in many renewable energy supply chains. This thesis aims to explore two main research questions: i) What are the geopolitical implications of China’s renewable energy strategies? and ii) What are China’s geopolitical motives behind renewable energy strategies? The main aim of this thesis is to analyze how the changes in China’s role are shaping transformations of the world order and to draw conclusions on the implications for the field of geopolitics. This thesis will focus its research on qualitative review of the current state of knowledge on a wide range of topics relating to geopolitics, energy, security, and renewable energy sources. The case study of China’s involvement in cobalt mining in Democratic Republic of Congo constitutes the methodological basis of this thesis.